A successful outcome of pregnancy with Berger disease - Mishra, Vineet V.; Rane, Priyanka H.; Aggarwal, Rohina; Shah, Kunur N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
With the increasing prevalence of chronic kidney disease (CKD) in the general population, female patients of fertile age with impaired kidney function are becoming more common. The presence of CKD in pregnant patients has been associated with poorer pregnancy outcomes. IgA nephropathy is the most common glomerulonephritis worldwide. The outcome of pregnancy in patients with CKD is related to impaired glomerular filtration rate and the degree of proteinuria. In non-aggressive IgA nephropathy, there is traditionally a slow progression to chronic kidney failure in 25–30% of cases during a period of 20 years. Women with immunoglobulin g A nephropathy (IgAN) are at higher risk of hypertension, preeclampsia, and fetal loss; the prognosis is worse for those who have advanced chronic kidney disease and proteinuria. Here we present two case reports who successfully delivered having aggressive IgA nephropathy and chronic hypertension in pregnancy.